PENGARUH INTENSITAS INTERAKSI SOSIAL PESERTA DIDIK TERHADAP TINGKAT RELIGIUSITAS PESERTA DIDIK DI SMP IT - Salmun Kaulan; Yunindyawati Yunindyawati; Waspodo Waspodo (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to determine the effect of the intensity of social interaction of students on the level of religiosity of students at the Harapan Mulia Integrated Islamic Junior High School Palembang and to determine the influence of the intensity of social interaction of students on the level of religiosity of students at the Harapan Mulia Integrated Islamic Junior High School Palembang. This type of research is quantitative. The instrument used in collecting data is a Likert scale model questionnaire. The population of the study, namely the students of Harapan Mulia Palembang Integrated Islamic Middle School as many as 299 people with a sample of 70 people through a proportionate stratified random sampling technique. The results of the study found that there was a significant influence between the intensity of social interaction on the level of religiosity of SMP IT Harapan Mulia Palembang students. This can be proven by the results of hypothesis testing using Linear Regression Analysis. This test obtained a sig value of 0.000 and an α value (0.000 <0.05), then Hₒ was rejected and Hₐ was accepted. By accepting Hₐ as a result of the analysis, it means that there is a significant effect of the intensity of social interaction on the level of religiosity of SMP IT Harapan Mulia Palembang students. The test results for the coefficient of determination R Square is 0.874, indicating that the variable intensity of social interaction is able to explain the variable level of religiosity of 87.4% in other words, 87.4% of the level of religiosity is determined by the intensity of social interaction carried out by students, while the rest is 12. 6% is influenced by other factors not examined in this study